Pengaruh Religiusitas dan Etos Kerja Islami Terhadap Kinerja Karyawan Bank Kaltimtara Syariah Kota Samarinda - Siska Sari Maulinda; Purwanti Purwanti; Sri Wahyuni (RJABM (Research Journal of Accounting and Business Management), 2025)
Employee performance is an important aspect in supporting the operational success of an organization, especially in the Islamic banking sector which demands the implementation of Islamic values. Improving employee performance must be managed systematically, because the factors that influence it, such as religiosity and work ethic based on Islamic values, are complex and interrelated. This study was conducted to analyze the influence of religiosity and work ethic based on Islamic values on employee performance at Bank Kaltimtara Syariah, Samarinda City, considering the importance of human resource management based on Islamic values. The study used a quantitative method with data collection techniques through questionnaires filled out by 36 respondents. The results showed that religiosity (X1) had a significant influence on employee performance with a t value of 4.060 and a significance of 0.000, while work ethic Islamic (X2) also had a significant influence with a t value of 2.489 and a significance of 0.018. This study provides practical recommendations for improving human resource management by strengthening the implementation of Islamic values in the work environment. Suggestions that can be given for further research are to increase the number of respondents and use other variables to provide a deeper understanding of the factors that influence employee performance.